Unsteady Flow And Heat Transfer Past A Stretching/Shrinking Sheet In A Hybrid Nanofluid - Pop, Ioan Mihai; Waini, Iskandar; Ishak, Anuar (Elsevier Ltd, 2019)
The unsteady flow and heat transfer past a stretching/shrinking sheet in a hybrid nanofluid is studied. The governing equations of the problem are transformed to the similarity equations by using similarity transformation technique. The problem is solved numerically using the boundary value problem solver (bvp4c) in Matlab software. The plots of the skin friction coefficient and the local Nusselt number as well as the velocity and temperature profiles for selected parameters are presented. It is found that dual solutions exist for a certain range of the unsteadiness parameter. A temporal stability analysis is performed to determine the stability of the dual solutions in a long run, and it is reveals that only one of them is stable while the other is unstable.